2016
DOI: 10.3389/fnagi.2016.00307
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Structural and Functional Frontostriatal Connectivity Predicts Self-Control in the Healthy Elderly

Abstract: Self-regulation refers to the successful use of executive functions and initiation of top-down processes to control one's thoughts, behavior, and emotions, and it is crucial to perform self-control. Self-control is needed to overcome impulses and can be assessed by delay of gratification (DoG) and delay discounting (DD) paradigms. In children/adolescents, good DoG/DD ability depends on the maturity of frontostriatal connectivity, and its decline in strength with advancing age might adversely affect self-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…One German-based study investigated functional and structural connectivity associations with a delay of gratification and a delay discounting paradigm in 40 healthy older adults (mean age = 74) using predefined 90-node and 12-node brain region networks (Hanggi et al 2016). Functional and structural connections between nodes located in the frontostriatal regions were implicated after controlling for age, sex, intracranial volume, and head motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One German-based study investigated functional and structural connectivity associations with a delay of gratification and a delay discounting paradigm in 40 healthy older adults (mean age = 74) using predefined 90-node and 12-node brain region networks (Hanggi et al 2016). Functional and structural connections between nodes located in the frontostriatal regions were implicated after controlling for age, sex, intracranial volume, and head motion.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally examined whether results remained significant after further adjusting for cognitive function. One prior study investigated temporal discounting associations with DTI measures using a set of predefined regions of interest in 40 healthy older adults (Hanggi et al 2016). We investigated this using a voxelwise whole-brain approach in more than 300 older adults without dementia from the Rush Memory and Aging Project, a longitudinal clinicopathologic study of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the caudate activity was linked to reward valuation in the delay‐discounting task, which may correspond to the outcome evaluation function of the caudate . Interestingly, any abnormalities in the caudate with regard to task‐related activation or resting‐state functional connectivity (most commonly between the caudate and the ventral PFC) were coupled to higher choice impulsivity . In sum, the caudate may be crucial for the cognitive control of choice impulsivity, presumably via activity‐dependent reward valuation processing (Fig.…”
Section: Evidence From Human Neuroimaging Studiesmentioning
confidence: 94%
“…Interestingly, Hampton and colleagues reported that the structural connectivity from the dorsal striatum to the dlPFC was positively associated with discounting propensity, which seems to oppose the general finding from DTI studies . However, Hampton and colleagues reconciled this conflict, particularly with the study of van den Bos and colleagues, by suggesting that the stronger frontostriatal WM connectivity, comprising the dorsal/ventral part of the dorsal striatum, may be correlated respectively with higher/lower choice impulsivity.…”
Section: Evidence From Human Neuroimaging Studiesmentioning
confidence: 97%
See 1 more Smart Citation